Pengaruh Kompetensi dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pada Hotel Jayakarta Lombok - Aryghi, Imam Sultan; Suryatni, Mukmin; Wahyulina, Sri (Postgraduate, University of Mataram, 2024)
This study aims to find out: (1) the influence of competence on employee work productivity at Hotel Jayakarta Lombok, (2) the effect of work discipline on work productivity at Hotel Jayakarta Lombok, and (3) the effect of competence and work discipline on employee work productivity at Hotel Jayakarta Lombok. This research includes causal associative research using a quantitative approach. The population of this study is all employees of Hotel Jayakarta Lombok which totals 115 people. Thus, the number of respondents used in this study is 90 people. Data was collected with questionnaires that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results of the study at the significance level of 5% showed that: (1) there was a positive and significant influence of competence on employee work productivity at Hotel Jayakarta Lombok. This is evidenced by the tcount > ttable, which is 3,015 > 1,987 and the significance level is 0.003 < 0.025; (2) there is a positive and significant influence of work discipline on employee work productivity at Hotel Jayakarta Lombok. This is evidenced by the tcount < ttable, which is 3,196 > 1,987 and the significance level is 0.002 > 0.025; and (3) there is a positive and significant influence of competence and work discipline on the work productivity of employees at the Jayakarta Hotel Lombok. This is evidenced by the results of Fcount > Ftable which are 10,780 > 3,098.